2021
DOI: 10.1002/cti2.1264
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immunity to human coronaviruses is widespread but low in magnitude

Abstract: Objectives. Endemic human coronaviruses (hCoVs) circulate worldwide but cause minimal mortality. Although seroconversion to hCoV is near ubiquitous during childhood, little is known about hCoV-specific T-cell memory in adults. Methods. We quantified CD4 T-cell and antibody responses to hCoV spike antigens in 42 SARS-CoV-2-uninfected individuals. Antigen-specific memory T cells and circulating T follicular helper (cTFH) cells were identified using an activation-induced marker assay and characterised for memory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Previous work has suggested that substantial immune memory involving both arms of adaptive immune memory is generated against CCC 17,23,25,26 . We observed that about 72-81% of subjects exhibited immune CD4+ T cell memory responses to each of the 4 CCC studied, consistent with frequencies detected in both community and heath care works cohorts 26 , and similar to the findings of Tan et al 25 . Remarkably, we found a stable and sustained T cell and antibody response against CCC which are supported by recent experimental findings from Cohen et al 41 or mathematical modeling 19,20 and argues against the short-lived nature of CCC responses [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has suggested that substantial immune memory involving both arms of adaptive immune memory is generated against CCC 17,23,25,26 . We observed that about 72-81% of subjects exhibited immune CD4+ T cell memory responses to each of the 4 CCC studied, consistent with frequencies detected in both community and heath care works cohorts 26 , and similar to the findings of Tan et al 25 . Remarkably, we found a stable and sustained T cell and antibody response against CCC which are supported by recent experimental findings from Cohen et al 41 or mathematical modeling 19,20 and argues against the short-lived nature of CCC responses [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that substantial immune memory involving both arms of adaptive immune memory is generated against CCC 17,23,25,26 . We observed that about 72-81% of subjects exhibited immune CD4+ T cell memory responses to each of the 4 CCC studied, consistent with frequencies detected in both community and heath care works cohorts 26 , and similar to the findings of Tan et al 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations